Which patients would benefit from computed tomography coronary angiogram (CTCA) for evaluation of coronary artery disease (CAD)?. Issue 9 (September 2016) - Madrigal, Tamer; Hamilton, Frank
Abstract : Evidence‐Based Answer : CTCA is beneficial to rule out significant CAD in patients experiencing chest pain who have low to intermediate risk, with negative likelihood ratios ranging from 0.02 to 0.08 (SOR: B, meta‐analyses of cohort studies with overlap of studies). CTCA has also been shown to be cost effective in diagnosing CAD when compared with standard of care approaches (SOR: B, decision analytic model applied to cohort level study).